Bacteremia caused by Slackia exigua: A report of two cases and literature review. Issue 1 (January 2020) - Kawasuji, Hitoshi; Kaya, Hiroyasu; Kawamura, Takayuki; Ueno, Akitoshi; Miyajima, Yuki; Tsuda, Takeshi; Taniguchi, Hirokazu; Nakamura, Masahiko; Wada, Akinori; Sakamaki, Ippei; Niimi, Hideki; Yamamoto, Yoshihiro
Abstract: Slackia exigua is an obligate anaerobic coccobacillus associated with dental infection, but rarely causes extraoral infection. We report two cases of monomicrobial bacteremia caused by S. exigua isolated from two institutions. The first case involved community-acquired bacteremia associated with pleural empyema in a 69-year-old man. The second case involved hospital-acquired bacteremia secondary to postoperative intra-abdominal abscess in a 73-year-old man with primary intestinal diffuse large B-cell lymphoma. S. exigua was finally identified by 16S ribosomal RNA gene sequencing analyses in both cases. In the first case, our attempts to identify the organism using commercial identification kits for anaerobes resulted in inaccurate identification as Gemella morbillorum . However, S. exigua was promptly identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry in the second case. The epidemiology and clinical characteristics of S. exigua extraoral infection remain unclear because of the limitations in accurate identification and because only 19 cases of extraoral S. exigua infection have been reported previously, including four cases of bacteremia. Physicians should focus on this species, which can cause community-acquired infections and spread via various routes even in patients with no comorbidities. Further studies are needed to clarify the clinical characteristics of extraoral S. exigua infections.